Basic Statistics Relating to Assam's Economy 1950-51 to 1961-62 Department of Economics and Statistics Government of Assam - Planning Commission (Planning Commission, 1963)
In this brochure, the Second in the series issued by this Department, an attempt has been made to present a statistical picture of the growth of the State’s economy during the periods of Five Year Plans as compared with the position in the pre-Plan year 1950-51. Figures relating to various sectors of the economy are presented for the pre-Plan year 1950-51, the last year of the First Plan 1955-56, and year by year thereafter up to 1961-62. There are, however, some variations here and there depending upon availability of data. The first section consisting of seven tables show a few key indicators of the economy.
Department of Economics and Statistics Government of Assam